Java in a nutshell - Flanagan, David (O'Reilly, 2005)
With more than 700,000 copies sold to date, Java in a Nutshell from O'Reilly is clearly the favorite resource amongst the legion of developers and programmers using Java technology. And now, with the release of the 5.0 version of Java, O'Reilly has given the book that defined the "in a Nutshell" category another impressive tune-up. In this latest revision, readers will find Java in a Nutshell , 5th Edition, does more than just cover the extensive changes implicit in 5.0, the newest version of Java. It's undergone a complete makeover--in scope, size, and type of coverage--in order to more closely meet the needs of the modern Java programmer. To wit, Java in a Nutshell , 5th Edition now places less emphasis on coming to Java from C and C++, and adds more discussion on tools and frameworks. It also offers new code examples to illustrate the working of APIs, and, of course, extensive coverage of Java 5.0. But faithful readers take comfort: it still hasn't lost any of its core elements that made it such a classic to begin with. This handy reference gets right to the heart of the program with an accelerated introduction to the Javaprogramming language and its key APIs--ideal for developers wishing to start writing code right away. And, as was the case in previous editions, Java in a Nutshell , 5th Edition is once again chock-full of poignant tips, techniques, examples, and practical advice. For as longas Java has existed, Java in a Nutshell has helped developers maximize the capabilities of the program's newest versions. And this latest edition is no different.